A new rigorous two-phase kinetic model for accurate prediction of the asphaltene deposition rate during the oil flow in porous media of petroleum reservoirs. (2nd May 2016) - ZareNezhad, Bahman; Sadi, Maryam; Parsa, Hanieh
ABSTRACT: Asphaltene formation and deposition in oil reservoirs are the most important problems in petroleum industry. A new rigorous two-phase kinetic model for simulation of flow behavior considering the asphaltene deposition process is presented in this work. All governing equations considering the proposed new adsorption kinetic model are solved by finite difference method. The presented model is validated using the most accurate available data and different oil samples. The proposed approach can be used for accurate evaluation of the effect of asphaltene deposition on the oil flowing condition in porous media of petroleum reservoirs.